Gambaran Kualitas Hidup Penderita Diabetes Melitus Tipe II di Wilayah Kerja Puskesmas Tompaso - Idayanti Pindan; Theo Muatang; Lucyana Leonita Pongoh (Jurnal Ilmiah Kesehatan, 2025)
Diabetes Mellitus is a disease that is difficult to cure so that it will have an impact on the quality of life of sufferers in various conditions such as physical, psychological, social and environmental conditions. This study aims to describe the quality of life of type II diabetes melitust sufferers in the Tompaso Health Center working area. The method used in this study is descriptive with a Cross Sectional approach. The population of this study were patients with type II diabetes mellitus in the Tompaso Health Center work area. The sample in this study were 81 respondents, the sampling technique used total sampling. The results showed that most respondents had good quality of life as many as 43 (53.1%) people and poor quality of life as many as 38 (46.9%) people. Thus it can be concluded that the quality of life of type II diabetes mellitus patients in the Tompaso Health Center work area is in the good category as many as 43 (53.1%) people. Suggestions are expected with this research, can be input or information and can improve the quality of services that can support interventions and improve the quality of life of people with diabetes mellitus.